Increased risk of infections and infection-related mortality in children undergoing haematopoietic stem cell transplantation compared to conventional anticancer therapy: a multicentre nationwide study. (February 2016) - Styczynski, J.; Czyzewski, K.; Wysocki, M.; Gryniewicz-Kwiatkowska, O.; Kolodziejczyk-Gietka, A.; Salamonowicz, M.; Hutnik, L.; Zajac-Spychala, O.; Zaucha-Prazmo, A.; Chelmecka-Wiktorczyk, L.; Siewiera, K.; Fraczkiewicz, J.; et al.
Abstract: This nationwide multicentre study analysed the epidemiology of bacterial, viral and fungal infections in paediatric haematopoietic stem cell transplantation (HSCT) and paediatric haematology and oncology (PHO) patients over a period of 24 consecutive months, including incidence, hazard risk and outcome of infections as well as occurrence of multidrug-resistant bacteria. During this period, 308 HSCTs were performed and 1768 children were newly diagnosed for malignancy. Compared to PHO, the risk in HSCT patients was significantly higher for all infections (hazard ratio (HR) 2.7), bacterial (HR 1.4), fungal (HR 3.5) and viral (HR 15.7) infections. The risk was higher in allo- than auto-HSCT for bacterial (HR 1.4), fungal (HR 3.2) and viral (HR 17.7) infections. The incidence of resistant bacteria was higher in HSCT than in PHO patients for both G-negative (72.5% vs. 59.2%) and G-positive (41.4% vs. 20.5%) strains. Cumulative incidence of bacterial, fungal and viral infections in HSCT patients was 33.9, 22.8 and 38.3%, respectively. Cumulative incidence of viral infections in allo-HSCT was 28.0% for cytomegalovirus, 18.5% for BK virus, 15.5% for Epstein-Barr virus, 9.5% for adenovirus, 2.6% for varicella zoster virus, 0.9% for influenza, 0.9% for human herpesvirus 6 and 0.3% for hepatitis B virus. Survival rates from infections were lower in HSCT than in PHO patients in bacterial (96.0 vs. 98.2%), fungal (75.5 vs. 94.6%) and most viral infections. In conclusion, the risk of any infections and the occurrence of resistant bacterial strains in allo-HSCT patients were higher than in auto-HSCT and PHO patients, while the outcome of infections was better in the PHO setting.